2011
DOI: 10.1371/journal.pone.0015864
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 σ Expression Effects G2/M Response to Oxygen and Correlates with Ovarian Cancer Metastasis

Abstract: Background In vitro cell culture experiments with primary cells have reported that cell proliferation is retarded in the presence of ambient compared to physiological O2 levels. Cancer is primarily a disease of aberrant cell proliferation, therefore, studying cancer cells grown under ambient O2 may be undesirable. To understand better the impact of O2 on the propagation of cancer cells in vitro, we compared the growth potential of a panel of ovarian cancer cell lines under ambient (21%) or physiological (3%) O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Briefly, 10 6 cells per mL of complete RPMI 1640 medium treated with darinaparsin for 24 or 48 hours was harvested, washed with ice cold PBS and stained with Annexin-V-FITC antibody and PI for 15 minutes and the samples were analyzed by flow cytometry within 1 hour. For cell cycle analysis, darinaparsin treated cells were harvested, washed in ice cold PBS, fixed in ethanol and stained with PI staining, as discussed before (9). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 10 6 cells per mL of complete RPMI 1640 medium treated with darinaparsin for 24 or 48 hours was harvested, washed with ice cold PBS and stained with Annexin-V-FITC antibody and PI for 15 minutes and the samples were analyzed by flow cytometry within 1 hour. For cell cycle analysis, darinaparsin treated cells were harvested, washed in ice cold PBS, fixed in ethanol and stained with PI staining, as discussed before (9). …”
Section: Methodsmentioning
confidence: 99%
“…(9) Primary antibodies validated against total or phospho B-Raf (Ser445), c-Raf (Ser338) MAPK (Erk1/2)Thr202/Tyr204, MEK (Ser217/221),SHP1, AKT, mTOR (Ser2448), p70S6K (Thr389), PI3K- p85-Tyr458/p55-Tyr199, Foxo3a (Ser253), Bcl-2, Bim, c-myc, eIF4E (Ser209), 4E-BP1 (Thr37/46), total and cleaved caspase-3, 8, 9 and PARP were purchased from Cell Signaling Technology (Beverly, MA). For co-immunoprecipitation experiment, 200µg of protein lysate was used, precleared with Protein A agarose beads (Cell Signaling Technology, Beverly, MA) followed by overnight incubation with primary antibody (SHP1 or ERK1/2, 1:50 dilution, validated for immunoprecipitation, Cell Signaling Technology, Beverly, MA), followed by precipitation with 30µl of Protein A agarose beads (50% slurry).…”
Section: Methodsmentioning
confidence: 99%
“…This study highlights that metastasis of ovarian cancer is an early event since a protein involved in this behavior can be detected as a biomarker for early ovarian cancer. In another study, another member of the 14-3-3 familly, 14-3-3 sigma, has been found to protect the cancer against oxidative stress by inducing an insensitiveness of the cells to high O 2 concentrations [172].…”
Section: Specific Mechanisms Underlying Ovarian Cancer Metastasismentioning
confidence: 96%
“…Cultures were grown in 5% CO 2 under 3% oxygen tension to mimic physiological conditions (41). Prior to treatment with UV light, cells were washed with 1ϫ Hanks' balanced salt solution, medium was removed, and the culture was exposed to 200 J/m 2 UV light using a Spectrolinker XL-1500 UV cross-linker.…”
Section: Methodsmentioning
confidence: 99%